'Not All Claims Are Representative Claims': Constructing 'The People' in Post-Representative Movements. Issue 4 (2nd October 2021) - Zicman de Barros, Thomás
ABSTRACT: The article argues that the eruption of 'indignation' protests after 2011 produced new discourses questioning political representation that challenge one of the most important frameworks of the constructivist turn in democratic theory: Michael Saward's representative claim. This article analyses these post-representative claims through Gayatri Chakravorty Spivak's distinction between Vertretung (or representation as 'acting for') and Darstellung (aesthetic and performative representation), and concludes that it is possible to discursively construct 'the people' without implying representation as 'stepping in someone's place'.